IL28B polymorphism and early anemia predict the rapid null response in genotype‐1 chronic hepatitis C with dual therapy. Issue 4 (18th February 2015) - Teng, Wei; Chang, Tzu‐Ching; Huang, Chien‐Hao; Jeng, Wen‐Juei; Chen, Wei‐Ting; Huang, Chang‐Wen; Ho, Yu‐Pin; Lin, Chun‐Yen; Sheen, I‐Shyan
Summary: Background and aims: Rapid null response (rNR), defined as less than one log decline of Hepatitis C virus (HCV‐RNA) at Week 4 of treatment with pegylated interferon‐α and ribavirin (PegIFN/RBV), is highly correlated with treatment failure in patients with chronic hepatitis C (CHC), genotype‐1 (GT‐1). In this study, we investigate the possible predictors of rNR. Methods: We retrospectively analyzed a cohort of 199 GT‐1 CHC naive patients who had been treated with a dual therapy of PegIFN/RBV. Clinical parameters and genotypes of rs12979860, the single nucleotide polymorphisms (SNPs) of interleukin‐28B ( IL28B ) were analyzed for their relationship with rNR. Results: Of the patients analyzed, 41.7% did not exhibit a rapid virological response (RVR). Only 13.1% of patients who experienced a rNR showed an RVR. The treatment failure rate was 36.2%. High baseline viral load (OR: 5.74; p = 0.028), nonrapid virological response (non‐RVR; OR: 4.32; p = 0.004) and rNR (OR: 51.82; p < 0.001) were the predictors of treatment failure. In addition, both the non‐CC allele of rs12979860 (OR: 13.8; p < 0.001) and the Hb (hemoglobin) decline to < 3 g/dL within 4 weeks of treatment (no early anemia; OR: 4.6; p = 0.024) were predictors of rNR. Conclusions: rNR predicted treatment failure early in GT‐1 CHC patients treated with PegIFN/RBV. Non‐CC genotype of rs12979860 and no early anemia were significant predictors of rNR.